Context‐dependent regulation of Th17‐associated genes and IFNγ expression by the transcription factor NFAT5. Issue 1 (6th September 2016) - Alberdi, Maria; Iglesias, Marcos; Tejedor, Sonia; Merino, Ramón; López‐Rodríguez, Cristina; Aramburu, Jose
Abstract : Stress‐activated transcription factors influence T‐cell function in different physiopathologic contexts. NFAT5, a relative of nuclear factor κB and the calcineurin‐activated NFATc transcription factors, protects mammalian cells from hyperosmotic stress caused by the elevation of extracellular sodium levels. In T cells exposed to hypernatremia, NFAT5 not only induces osmoprotective gene products but also cytokines and immune receptors, which raises the question of whether this factor could regulate other T‐cell functions in osmostress‐independent contexts. Here we have used mice with a conditional deletion of Nfat5 in mature T lymphocytes to explore osmostress‐dependent and ‐independent functions of this factor. In vitro experiments with CD4 T cells stimulated in hyperosmotic medium showed that NFAT5 enhanced the expression of IL‐2 and the Th17‐associated gene products RORγt and IL‐23R. By contrast, NFAT5‐deficient CD4 T cells activated in vivo by anti‐CD3 antibody exhibited a different activation profile and were skewed towards enhanced interferon γ (IFNγ) and IL‐17 expression and attenuated Treg responses. Using a model of experimental colitis, we observed that mice lacking NFAT5 in T cells exhibited exacerbated intestinal colitis and enhanced expression of IFNγ in draining lymph nodes and colon. These results show that NFAT5 can modulate different T‐cell responses depending on stress conditions and stimulatory context.